Military Architecture and the Four-Spāhbed System for Defense of the Sasanian Empire (224-651 CE) - FARROKH, Kaveh; KARAMIAN, Gholamreza; KARAMIAN, Hamid (Historia i Świat, 2021)
This article examines Sasanian military architecture with respect to its integration with the four-region Spāhbed system (Ādurbādagān-Spāhbed, Xwarāsān-Spāhbed, Xwarbārān-Spāhbed and Nēmrōz-Spāhbed) for defending the empire. Following an overview of Sasanian military architecture within Iran, the article examines the Darband wall of the Caucasus in the context of the office of the Ādurbādagān-Spāhbed facing the empire’s north and northwest (Ādurbādagān, Media Atropatene corresponding with the historical Azerbaijan in Iran’s northwest), the Tammisha and Gorgan wall systems of the Xwarāsān-Spāhbed facing the nomadic warrior peoples of the Central Asia, the military architecture of the Xwarbārān-Spāhbed facing the western (Romano-Byzantine) frontiers, and the Khandaq-e Shapur of the Nēmrōz-Spāhbed facing the southwest, notably raiders from the Arabian Peninsula threatening the empire’s southwest marches.